2017
DOI: 10.3389/fpsyg.2017.01691
|View full text |Cite
|
Sign up to set email alerts
|

Ideal Standards, Acceptance, and Relationship Satisfaction: Latitudes of Differential Effects

Abstract: We examined whether the relations of consistency between ideal standards and perceptions of a current romantic partner with partner acceptance and relationship satisfaction level off, or decelerate, above a threshold. We tested our hypothesis using a 3-year longitudinal data set collected from heterosexual newlywed couples. We used two indicators of consistency: pattern correspondence (within-person correlation between ideal standards and perceived partner ratings) and mean-level match (difference between idea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…For example, recent research suggests that individuals tend to enter new relationships with others possessing traits that closely correspond to their own ideal standards (Campbell, Chin, & Stanton, 2016;Gerlach, Arslan, Schultze, Reinhard, & Penke, 2017). Research has also demonstrated that individuals are more satisfied in relationships when they perceive smaller discrepancies between their ideal standards and partner perceptions (Buyukan-Tetik, Campbell, Finkenauer, Karremans, & Kappen, 2017;Campbell, Simpson, Kashy, & Fletcher, 2001;Fletcher et al, 1999;Fletcher, Simpson, & Thomas, 2000). Further, individuals are more apt to attempt to regulate (i.e., change) their partners when they perceive relatively large discrepancies between ideal standards and partner evaluations (Overall, Fletcher, & Simpson, 2006;Overall, Fletcher, Simpson, & Sibley, 2009).…”
Section: Perceived Mate Valuementioning
confidence: 99%
“…For example, recent research suggests that individuals tend to enter new relationships with others possessing traits that closely correspond to their own ideal standards (Campbell, Chin, & Stanton, 2016;Gerlach, Arslan, Schultze, Reinhard, & Penke, 2017). Research has also demonstrated that individuals are more satisfied in relationships when they perceive smaller discrepancies between their ideal standards and partner perceptions (Buyukan-Tetik, Campbell, Finkenauer, Karremans, & Kappen, 2017;Campbell, Simpson, Kashy, & Fletcher, 2001;Fletcher et al, 1999;Fletcher, Simpson, & Thomas, 2000). Further, individuals are more apt to attempt to regulate (i.e., change) their partners when they perceive relatively large discrepancies between ideal standards and partner evaluations (Overall, Fletcher, & Simpson, 2006;Overall, Fletcher, Simpson, & Sibley, 2009).…”
Section: Perceived Mate Valuementioning
confidence: 99%
“…These discrepancies have important implications for how individuals evaluate their relationships. Smaller ideal-partner discrepancies have been found to be associated with higher levels of relationship satisfaction and a lower likelihood of relationship dissolution (Fletcher et al, 2000 ; Campbell et al, 2001 ; Buyukcan-Tetik et al, 2017 ). In contrast, larger ideal-partner discrepancies are associated with lower relationship satisfaction and greater attempts at regulating a partner's behavior as a way to reduce the size of the discrepancy (Overall et al, 2006 , 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Expanding the standard evolutionary account of mate selection, a second major plank of the ISM is that the match between ideal standards and perceptions of a potential or current partner—we term here ideal-partner matching—should influence various outcomes in relationships, including the evaluations of partners and relationships and attempts to regulate or change partners or relationships to more closely match ideals (see Fletcher et al, 1999). Research testing this model has generally found good support for these predictions, showing that a better match between perceptions of specific partner attributes and corresponding ideal standards predicts higher levels of relationship satisfaction (Buyukcan-Tetik et al, 2017; Campbell et al, 2013; Fletcher et al, 1999, 2000), and lower desire for and attempts to change partners (Overall et al, 2006). Thus, a central evidence-based claim of the ISM is that mate selection and relationship outcomes are not simply a function of general positive versus negative perceptions of potential or existing partners, but rather the extent to which perceptions along central mate-selection dimensions match corresponding ideal standards.…”
mentioning
confidence: 94%